2017
DOI: 10.1249/mss.0000000000001234
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Land or Water Exercise in Pregnancy on Outcomes

Abstract: Exercise performed on land is more effective than aquatic activities in preventing excessive maternal weight gain, whereas combined programs (land + aquatic) or water exercise programs may be more effective in preventing gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Exercise during pregnancy is considered beneficial to both mother and fetus and is recommended by the Colleges of Obstetricians and Gynecologists ( 30 , 31 ). Several risk factors such as diabetes mellitus ( 32 ) and preeclampsia, commonly associated to premature delivery ( 33 , 34 ) can be reduced by physical exercise ( 35 , 36 ). Preclinical studies evidenced that pups born from exercised mothers had significantly higher brain, liver, heart and kidney weights compared to the controls, which suggests that regular exercise during pregnancy can improve placentary functioning and support fetal development ( 37 , 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise during pregnancy is considered beneficial to both mother and fetus and is recommended by the Colleges of Obstetricians and Gynecologists ( 30 , 31 ). Several risk factors such as diabetes mellitus ( 32 ) and preeclampsia, commonly associated to premature delivery ( 33 , 34 ) can be reduced by physical exercise ( 35 , 36 ). Preclinical studies evidenced that pups born from exercised mothers had significantly higher brain, liver, heart and kidney weights compared to the controls, which suggests that regular exercise during pregnancy can improve placentary functioning and support fetal development ( 37 , 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite concerns about the safety of aquatic exercises during pregnancy, the procedure in our study proved to be safe for pregnant women with hypertension and controls in the third trimester of pregnancy. Barakat et al 26 also demonstrated the safety of exercise practice among pregnant women. These authors compared the effects of exercise on pregnant women, concluding that while land exercises were more effective at preventing maternal weight gain, aquatic or combined programs involving land and water were more effective at preventing gestational diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…These authors compared the effects of exercise on pregnant women, concluding that while land exercises were more effective at preventing maternal weight gain, aquatic or combined programs involving land and water were more effective at preventing gestational diabetes. 26 Bacchi et al, 27 evaluating 100 healthy pregnant women, concluded that three weekly sessions of aquatic activities during pregnancy prevent maternal overweight and preserve birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…in Canada in 2017, in a comparative study between the use of aerobics in water with exercise on land on the outcome of pregnancy, concluded that exercising on the dry land compared with exercising in water has the greatest effect on improving the weight of the pregnant mother, while exercising in water reduces maternal prevalence to gestational diabetes. [19] Vallim et al . in 2011, entitled “the effect of eco yoga on the quality of life in pregnancy” showed that eco-yoga did not improve the quality of life or the mood problems of pregnant women, and therefore suggested that this study be conducted in a larger research population and different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Conversely, in Canada, in 2017, in a comparative study between the use of aerobics in water with exercise on land on the outcome of pregnancy, it has been concluded that exercising on the land compared with exercise in water has the greatest effect on improving the weight of the pregnant mother, while exercising in water reduces maternal prevalence in gestational diabetes. [19]…”
Section: Introductionmentioning
confidence: 99%